Revisiting Donald Schön's notion of reflective practice: a Daoist interpretation. Issue 5 (2nd September 2020) - Tan, Charlene
ABSTRACT: This article revisits Donald Schön's notion of reflective practice by interpreting it from a Daoist perspective. In the first part of the essay, I summarise Schön's critique of technical rationality and his concept of reflection-in-action. I argue that two main weaknesses of Schön's approach to reflective practice are the presupposition of self-protected individualism, and an insufficient attention to ethical concerns. Next I expound on a Daoist formulation of reflective practice by drawing on the philosophical thought of Zhuangzi. Three salient characteristics are highlighted. First, Zhuangzi's thought is aligned with Schön's rejection of a technical approach and concomitant support of reflection-in-action. But unlike Schön's individualistic tendency, a dao -centric orientation is called for where the practitioner is cognisant of and synchronises oneself with the innate nature of all things. Thirdly, Zhuangzi foregrounds ethics by stressing the primacy of other-regarding considerations and harmonious responses for reflection-in-action. A Daoist understanding of reflective practice offers a non-Western philosophical basis to Schön's ideas and adds to the existing theories on reflection.